2004
DOI: 10.1057/palgrave.ejis.3000480
|View full text |Cite
|
Sign up to set email alerts
|

Potential of critical e-applications for engaging SMEs in e-business: a provider perspective

Abstract: Against a background of the low engagement of SMEs in e-business this paper investigates the emergence of, and potential for, critical e-applications defined as "an e-business application, promoted by a trusted third party, which engages a significant number of SMEs by addressing an important shared business concern within an aggregation." By a review of secondary data and empirical investigation with service providers and other intermediaries the research shows that such applications can facilitate the e-busi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 38 publications
5
124
0
1
Order By: Relevance
“…ASPs have successfully positioned themselves as 'trusted third parties' to remove this concern. Hence, the research confirms the importance of the role of intermediaries identified earlier by Swan and Newell (1995) and Brown and Lockett (2004). In terms of SMEs decision to adopt, from a strategic perspective, the interviews confirmed that there is no common model of adoption.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…ASPs have successfully positioned themselves as 'trusted third parties' to remove this concern. Hence, the research confirms the importance of the role of intermediaries identified earlier by Swan and Newell (1995) and Brown and Lockett (2004). In terms of SMEs decision to adopt, from a strategic perspective, the interviews confirmed that there is no common model of adoption.…”
Section: Resultssupporting
confidence: 76%
“…Other influencing factors are business sector and nature (Poon and Swatman, 1999;Fillis et al, 2004;Windrum and Berranger, 2002), owner's enthusiasm and growth ambition (Cragg and King, 1993;Poon and Swatman, 1999;Fillis et al, 2004), and location (Windrum and Berranger, 2002). The role of the intermediary as a means of facilitating the diffusion of complex ICT has been observed by a number of other authors (Swan and Newell, 1995;Newall et al, 2000;Brown and Lockett, 2004). A recent study by Levy and Powell (2003) Furthermore, a contingent model was developed incorporating these factors and the level of business value and business growth.…”
Section: Hosted Applications Adoption and Complexitymentioning
confidence: 97%
See 1 more Smart Citation
“…These measures are frequently manifested as expressions of the 'digital-divide'. The divide, however, is not restricted to individual access but is also reflected between large and small firms (Brown & Lockett, 2004) and in non-technology-related areas such as income and education. Clearly, there is no sense in governments creating online services that cannot be utilised by users, citizens and businesses due to lack of access attributed to prohibitive costs or poor infrastructure.…”
Section: Developing Countriesmentioning
confidence: 99%
“…In networks, when compared with chain, interactions are governed not only by the market or through formal mechanisms, but through the use of informal and mutual mechanisms (Brown, Locket, 2004) perceive the network as a highly developed form of collaboration, which has a high degree of structure and integration.…”
Section: Theoretical Basismentioning
confidence: 99%